Theoretical and Juridical Study of Environmental Pollution Crimes in the Mining Sector - Safera Dey Woi; Diana D. Putong; Feibe E. Pijoh (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Indonesia as a constitutional state mandates the protection of environmental quality, particularly in the mining sector which often causes significant pollution. This study aims to analyze the criteria of environmental pollution elements from theoretical and juridical perspectives, and to examine their application in handling mining sector pollution cases. Using normative legal research with statutory, conceptual, and comparative approaches, this study compares theoretical concepts (ecological, ethical, and philosophical) with positive law provisions under Law No. 32 of 2009 on Environmental Protection and Management. The findings reveal a fundamental discrepancy: theoretically, pollution is determined by ecological disruption and harm to ecosystems or human health, while juridically, pollution is strictly defined by exceeding pre-determined environmental quality standards (baku mutu). This disharmony is evident in the PT Newmont Minahasa Raya (Buyat Bay) case, where despite evident ecological damage and public health impacts, the court acquitted the defendants because laboratory results showed pollutant concentrations remained below the formal quality standards. The study concludes that the narrow juridical approach creates legal loopholes allowing actual polluters to escape criminal liability. Recommendations include revising Law No. 32/2009 to incorporate ecological impact criteria beyond rigid quality standards, and adopting a more holistic judicial approach that balances legal certainty with environmental justice. Keywords: environmental pollution, mining sector, theoretical criteria, juridical criteria, criminal liability, environmental justice